PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK: PENGHINDARAN PAJAK - Ade Maryani; Husnul Khotimah (JEKOS (Jurnal Ekonomi Dan Sosial), 2025)
This study aims to analyze the effect of profitability, leverage, and firm size on tax avoidance in health sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Tax avoidance has become a major concern in the field of taxation, especially in sectors that contribute significantly to public services. Companies in this sector tend to design efficient financial strategies to minimize their tax burdens. This research employs a quantitative approach using multiple linear regression analysis. The population of this study consists of 33 health sector companies, with 10 companies selected as samples using a purposive sampling method. The analysis results show that profitability and leverage have a significant effect on tax avoidance, while firm size has no significant effect on tax avoidance. Simultaneously, the three independent variables have a significant effect on tax avoidance. The insignificance of firm size may be due to increased fiscal supervision of large companies, which limits the space for tax avoidance practices. These findings emphasize the importance of tax regulations that are responsive to internal corporate strategies and enhance compliance through greater transparency and stricter oversight.   Keywords: Firm Size, Health Sector, Leverage, Profitability, Firm Size, Tax Avoidance.